Passado presente : anarquismo e construtivismo na educação brasileira - Marconi, Juliana Guedes dos Santos (2010)
The present research aims at reflecting about the contemporary educational anarchist methodology from the analysis of that one in relation to the educational constructivist theories. The emphasis of this work is on methodology since the purpose is not comparing or making approaches among the educational movements uttered or defended by anarchists or any other recent educational movements. In fact, besides the historical context, the political-ideological differences that constitute anarchist and constructivist concepts are evident. Thus, firstly, it was done an explanation regarding the anarchist movement and its aspects with emphasis to that dipped into the idealism that gave rise to the educational theories anarchists worked in this text. Then was discussed the main theoretical guidelines of anarchist education and, as an example of activity in the foreign context, La Escuela Moderna, Barcelonean institution created and managed by Francisco Ferrer y Guardia in the transition from the nineteenth to the twentieth century and, in the Brazilian context, the Escolas Modernas n.1 and n.2, the homonymous Barcelonean institution that were created in São Paulo. About the three institutions, the historical context, the main guidelines and them process of opening and closing, were mentioned. Thirdly, the theories of both, New School Movement and constructivism (established in the end of the twentieth century and based on the New School Movement) were analyzed. Fourthly, approaches between the methodologies developed not only by anarchist but also by constructivist initiatives were verified without forgetting the political-ideological differences, the contemporary educational anarchist methodology was analyzed. Finally, was possible to reflect on an educational theory that, although it is utopian and apprehensive, shows to be implicitly employed in educational environment. Besides, it was possible to reflect about issues as the recent detriment of teachers role and their performance and also the double possibility of employing methodologies adapted according to the political-ideological bases of each educational conception.